Income inequality, distributive unfairness, and support for democracy: evidence from East Asia and Latin America. Issue 8 (17th November 2019) - Wu, Wen-Chin; Chang, Yu-Tzung
ABSTRACT: Concern about rising economic inequality is widespread among ordinary citizens, academics, and policymakers. In particular, income inequality not only intensifies the conflicts between the rich and poor citizens but also leads to political instability. In this article, we investigate how income inequality is related to people's support for democracy by including both objective and subjective measures of inequality. Using data collected from 28 democracies in East Asia and Latin America during 2013 and 2015, we demonstrate that inequality, measured in either a subjective or objective way, decreases with people's satisfaction with democracy. In addition, we find that in East Asian countries, subjective measures of inequality, perceived unfairness of income inequality in particular, provide a better explanation of people's dissatisfaction with democracy than the Gini index, a commonly used objective measure of inequality. Our findings are robust to different model specifications and offer micro-level evidence suggesting that unfair income distribution undermines the consolidation of democracies.